If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*x-3 = 2/7 // - 2/7
(2/3)*x-(2/7)-3 = 0
(2/3)*x-2/7-3 = 0
2/3*x-23/7 = 0 // + 23/7
2/3*x = 23/7 // : 2/3
x = 23/7/2/3
x = 69/14
x = 69/14
| X^3-4x^2-16=0 | | 7(5-6x)=497 | | y^2-12y=-20 | | 8x^2-y^2=16 | | 75=-15p | | -6(7+x)=-102 | | 11v-3v=48 | | 3(-5+6x)=129 | | V=1/3~r2(h) | | -x-8=x+4 | | 3m^2n+12mn^2=0 | | 5.2(3+3x)-1.6=14 | | -2x-1=2x+7 | | 3=3x+1 | | 3(-5+2x)=9 | | X+6.3+5.6+8.4=27.4 | | 3.23-3.14x=2x-3.195 | | 7(-6-2x)=98 | | 2.5x+1.1=4.5 | | 10=2/3d | | 1.3x+8.8=3.1x-2 | | 10(3+x)=15(x-1)+1 | | -2/5-6 | | X^2+box+1=0 | | 12x+11+25x+2+69=360 | | 110=48-5x+7 | | -2x-1=x+20 | | 12x+11+25x+2=360 | | 10=-8(2x^2-2x-1) | | Cos^2x+6cosx+6=0 | | (X+9)(x-19)=0 | | 6(9+x)=102 |